(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article focuses on improving the system for assessing students’ physical fitness levels by grade in general education schools. The study analyzes the current state of physical education programs and proposes new approaches based on international experiences and Uzbekistan’s regulatory documents. It explores ways to enhance the system’s efficiency through age- and gender-adapted tests, the use of modern digital technologies, and teacher professional development. The research outcomes contribute to advancing physical education in schools and fostering a healthy generation.